If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -3x + -11 = -8x + 7 Reorder the terms: -11 + -8x + -3x = -8x + 7 Combine like terms: -8x + -3x = -11x -11 + -11x = -8x + 7 Reorder the terms: -11 + -11x = 7 + -8x Solving -11 + -11x = 7 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -11 + -11x + 8x = 7 + -8x + 8x Combine like terms: -11x + 8x = -3x -11 + -3x = 7 + -8x + 8x Combine like terms: -8x + 8x = 0 -11 + -3x = 7 + 0 -11 + -3x = 7 Add '11' to each side of the equation. -11 + 11 + -3x = 7 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 7 + 11 -3x = 7 + 11 Combine like terms: 7 + 11 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| 3x-10(x+2)=sqrt(13)-7x | | -8x-3x-11=-8+7 | | 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m | | X^2+5x+7=49 | | X^2+5x+58=0 | | R^3-r^2-4r+4=0 | | log(6x+8)=log(12) | | -7(8k-8)=-392 | | 720/6 | | 3cos^2x=2 | | 6tons=Pounds | | 720/3 | | Y=-1/2(x-6)(x8) | | 2(3x+2)=4(2x-5) | | 8s-26+5s-15=180 | | 6b+4b=-12+8b | | 25*7+11*3+2*3= | | 2x^2+-8x-384=0 | | 2(x+2)=-2(x+6) | | 44=x(5+6) | | 7x-(2x+5)=36 | | 2w-36=w-12 | | 46*7+87*3+21*3= | | W-12=2w-36 | | 1/3✖️3/4 | | 1/3✖️3/4=3/8 | | 29*7+16*3+8*3= | | 6y-14=9y-5 | | -3(y+2)=7y-8+4(2y+4) | | .027+2-.035x=0 |